Case Report: Intestinal Nodular Lymphoid Hyperplasia as First Manifestation of Activated PI3Kδ Syndrome Due to a Novel PIK3CD Variant - Marzollo, Antonio; Bresolin, Silvia; Colavito, Davide; Cani, Alice; Gaio, Paola; Bosa, Luca; Mescoli, Claudia; Rossini, Linda; Barzaghi, Federica; Perilongo, Giorgio; Leon, Alberta; Biffi, Alessandra; et al. (Frontiers in Pediatrics, 2021)
Nodular Lymphoid Hyperplasia (NLH) is a lymphoproliferative disease caused by non-clonal expansion of lymphoid cells in the gut mucosa. Little is known about the pathogenesis of NLH which is often disregarded as an insignificant or para-physiologic phenomenon. We present the case of a girl with isolated diffuse NLH (extending from the stomach to the rectum) caused by Activated PI3K-delta syndrome (APDS) due to the novel p.Glu525Gly variant in PIK3CD. The gain-of-function effect of the variant was confirmed by demonstration of overactivation of the Akt/mTOR pathway in patient’s cells. APDS diagnosis led to treatment with Sirolimus which resulted in the complete remission of NLH and in the prevention of extra-intestinal complications. In conclusion, we identify APDS as a novel cause of isolated NLH and suggest that patients with severe pan-enteric NLH should be screened for this disorder that may not be apparent on first-line immunological testing.